Sifat Mekanis Beton Dengan Menggunakan Steel Slag Sebagai Bahan Subtitusi Agregat Halus Dan Fly Ash Sebagai Bahan Subtitusi Semen - Yonna Rosianda; Alex Kurniawandy; Zulfikar Djauhari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The purpose of research is to identify the mechanical properties of concrete by using steel slag as subtitution for fine aggregates and fly ash as subtitution cement on concrete with the quality (f`c) 25 MPa. The research meant to review the permeability, porosity and load power of concrete. The proportion of steel slag and fly ash which was used is 0% and 20% of total weight of fine aggregates and cements. The permeability and porosity test was done on 28 days soaked concrete. For the pressure test, it was done on 28 days and 56 days soaked in normal water. The result of the test shown that the using of 20% steel slag and 20% fly ash liably improved the permeability and porosity of the concrete. On the normal concrete-pressure test, it was improved as well for 28 and 56 days soaked concrete. Meanwhile, the concrete with steel slag and fly ash as subtitution was also shown an improvement on 28 days and 56 days`s pressure test.Keywords : Steel slag, fly ash, Permeability, Porosity, Compressive strength.